Pengaruh Kerja Sama Tim, Motivasi Kerja dan Disiplin Kerja Terhadap Prestasi Kerja Karyawan Bank BNI KC Kediri - Wendy Septya Nugraha; Yogi Yunanto (MES Management Journal, 2026)
Banks have become an inseparable aspect of human life. They serve as institutions where people save money and apply for loans. The banking sector also plays a major role in strengthening a country’s economy. Work motivation refers to a condition that encourages individuals to carry out activities and perform their duties. Measuring employee performance is very important because it serves as the foundation for employee career development and opportunities for promotion. Performance appraisal can also motivate employees to contribute optimally to the organization. Several factors can influence employee performance, such as teamwork, motivation, and work discipline. Descriptive research aims to investigate certain situations or conditions, and the results are presented in the form of a research report. The findings indicate that teamwork, work motivation, and work discipline have a significant and simultaneous effect on employee performance.